Molecular genetic features of the development of restrictive cardiomyopathy in Russian children - K. V. Savostyanov; E. N. Basargina; E. E. Ryabova; A. A. Pushkov; I. S. Zhanin; E. Yu. Basargina; A. Yu. Alekseeva; L. V. Muraveva; L. A. Gandaeva; A. P. Fisenko (Российский кардиологический журнал)
Aim. To identify the proportion of restrictive cardiomyopathy (RCM), as well as cardiomyopathy (CMP) with a restrictive type of hemodynamics among all cases of genetic CMP and to determine the relative frequencies and spectrum of nucleotide variants in Russian children with RCM, as well as to search for phenogenotypic correlations.Material and methods. The study included 689 children with CMPs. All children underwent a molecular genetic testing of the target regions of 419 genes responsible for various cardiomyopathies and channelopathies using the method of massively parallel sequencing (MPS).Results. In 668 (97,0%) children, pathogenic, likely pathogenic nucleotide variants, as well as nucleotide variants with unknown clinical significance, were identified. Of these, 45 (6,7%) patients were selected to determine the molecular genetic characteristics of RCM, 20 of whom had clinical symptoms and morphofunctional structure of RCMP (3,0%), while the remaining 25 (3,7%) children were diagnosed with another CMP type with a restrictive type of hemodynamics. In total, these patients had 41 nucleotide variants in 15 different genes, while 19 (46,3%) variants were pathogenic, 12 (29,3%) — likely pathogenic, 10 (24,4%) — uncertain clinical significance. Pathogenic and likely pathogenic variants were identified in a total of 38 (84,4%) patients, while in 19 (42,2%) patients, the pathogenic variants described earlier were found. The most common genetic marker of RCM in Russian children was TNNI3 gene mutations. In total, they were identified in 12 (25%) children: with RCP — 8 (40%) patients; with CMP with a restrictive type of hemodynamics — 4 (16%) patients. At the same time, the most common mutation of the TNNI3 gene was the nucleotide variant c.575G>A, leading to the amino acid variant p.R192H, described earlier in patients with RCM and identified by us in three (15%) unrelated children with RCM. In addition, a significant difference was found between the averaged values of N-terminal pro-brain natriuretic peptide in patients with mutations in the MYH7 and TNNI3 genes (0,0039, p<0,05), as well as between the peak flow gradient values in children with mutations in TNNI3 and FLNC genes (0,0016, p<0,05), TNNI3 and MYH7 genes (0,039, p<0,05).Conclusion. The results of this study indicate a significant genetic heterogeneity of RCM in Russian children and the need for further research aimed at finding genotype-phenotype associations in order to predict the course of the disease and select the proper therapy.